Structural Design of Connection Methods for Well Control Controller Tubing Hanger - Wei, Peng; Li, Mingfei; Yao, Pengfei; Niu, Geng; Li, Han (Scientific Journal of Technology, 2026)
This paper conducts a systematic design of the connection structure between the well control controller and the tubing hanger, focusing on in‑depth analysis and strength verification of threaded connection methods. A comparison is made among four common connection forms—threaded, flanged, clamped, and welded connections—in terms of their characteristics and applicable conditions. The threaded connection scheme is finally selected. Detailed descriptions are given on the tooth‑profile design, basic parameters, and tensile‑strength calculation methods for both API buttress threads and triangular threads. In terms of structural design, a conical sealing‑surface structure employing dual‑step mating of internal and external threads is proposed to enhance the gas‑tightness and torque resistance of the connection. Finite‑element analysis is performed to verify the strength of the selected P110 steel API buttress thread joint, including the thread‑tooth strength and the tubing‑coupling tensile strength. The results show that under a given axial load of 200 kN, the ultimate load‑bearing capacity of the thread teeth is 377.4 kN, and the tubing tensile strength is 0.63 MPa, both meeting the operational requirements, thereby validating the feasibility and safety of the designed connection structure. This study provides a theoretical basis and engineering reference for the selection and strength assessment of tubing‑hanger connection methods in well‑control equipment.